Lower bounds on density for topologically nontrivial minimal cones up to dimension six - Jacob Bernstein; Lu Wang (Forum of Mathematics, Sigma, 2025)
We prove lower bounds on the density of regular minimal cones of dimension less than seven provided the complements of the cones are topologically nontrivial.